O cronotopo da prisão em textos de detentos inscritos em WriteAPrisoner.com - Silva, João Augusto Reich da (2023)
The main purpose of this study is to analyze the chronotopic relations emerging from inmates' presentation profiles registered in WriteAPrisoner.com, a website created to encourage and promote the reintegration of inmates through a correspondence exchange program. To better understand the chronotope of the prison and the specificities of the language of the subjects that constitute it, we established as corpus of analysis of this research the set of ten texts of inmates' presentation, analyzed in the light of the theoretical and methodological assumptions of the Dialogical Discourse Analysis, based on the writings of Bakhtin and the Circle. Through the discussion of basic concepts of the Bakhtinian thought as utterance, genres of discourse and dialogical relations, it was possible to describe the prison chronotope as a timespace marked by a slow and sluggish notion of time, which may or may not provide the inmates with self-knowledge and that prints in their discourses rhetorical-legal tones of guilt and innocence.